Posaconazole or isavuconazole as sole or predominant antifungal therapy for COVID-19-associated mucormycosis. A retrospective observational case series. (July 2022) - Soman, Rajeev; Chakraborty, Sourabh; Joe, Geethu
Highlights: Posaconazole/Isavuconazole were used to treat COVID-19 associated mucormycosis. Out of 28 consecutive patients, 21 patients were cured or improved. Of these, 2 deaths were directly attributable to mucormycosis. These outcomes compare favourably with those reported in the literature using AmB. It can be speculated that mucormycosis may be treated solely with these new Azoles. Abstract: The surge of COVID-19 associated Mucormycosis (CAM) in India during the second wave of COVID-19 led to lack of availability of amphotericin B(AmB). We retrospectively evaluated the outcome in 28 consecutive patients with CAM who received posaconazole (PCZ) or isavuconazole (ISVCZ) as sole or predominant therapy, based on factors like availability, affordability, site of infection or lack of treatment response. Therapeutic drug monitoring was used for PCZ in all cases & for ISVCZ in some cases. Higher trough levels were aimed to ensure therapeutic effect. Overall, 16 patients were cured, 5 patients improved, 6 patients died, of which 2 deaths were attributable to mucormycosis and 1 patient was lost to follow-up. The outcomes and survival were comparable to those reported in the literature. Although wider applicability of these results cannot be assumed, it leads to a speculation that treatment of mucormycosis with PCZ or ISVCZ, without AmB, is possible.